Promoting Safety in Culinary Training Laboratories: A Systematic Review of Strategies, Barriers, and Facilitators - Turmaningsih Surya Pratama; Bagoes Widjanarko; Daru Lestantyo; Yuliani Setyaningsih (Journal of Community Health Provision, 2026)
Educational kitchen laboratories present unique occupational safety challenges, yet systematic evidence on effective safety promotion remains fragmented. Young trainees are particularly vulnerable, with recent data indicating that workers aged 15-24 experience work-related injuries at rates up to 2.3 times higher than their adult counterparts. This underscores a pressing need for evidence-based safety interventions within vocational culinary education. This systematic literature review aimed to analyze safety promotion strategies and identify common barriers and facilitators in educational and vocational kitchen settings to propose an integrated safety framework. Guided by the PRISMA 2020 framework, a systematic search was conducted across the Scopus, PubMed, and Google Scholar databases for studies published between January 2015 and August 2025. From 5,124 initial records, 22 relevant studies were selected for synthesis after a rigorous screening process involving explicit inclusion/exclusion criteria. Thematic analysis was performed to synthesize the findings. The analysis revealed six key strategy themes: (1) educational interventions, (2) behavioral models, (3) technology-enhanced learning, (4) ergonomic improvements, (5) community-based learning, and (6) policy frameworks. Key barriers included persistent cognitive misconceptions (e.g., optimistic bias) and inadequate physical infrastructure. Conversely, critical facilitators involved the use of interactive and visual tools, strong institutional support, and stakeholder engagement. Promoting safety in culinary training environments requires a multidimensional approach that integrates behavioral, technological, and infrastructural strategies. This review synthesizes these determinants into a comprehensive framework, offering an evidence-based map for designing safer and more effective vocational education programs. Effective implementation is critical for fostering a resilient safety culture.